ACETAZOLAMIDE INDUCED SECONDARY ANGLE CLOSURE GLAUCOMA: A RARE CASE REPORT: Poster Presentation - Case Report - Resident - Atisundara, Siti Mutia; Rifada, R Maula; Umbara, Sonie; Gustianty, Elsa; Prahasta, Andhika (Majalah Oftalmologi Indonesia, 2023)
Introduction : Drugs such as topiramate, acetazolamide, methazolamide, buproprion, and trimethoprim- sulfamethoxazole potentially cause an elevation of IOP. Drug-induced glaucoma may be an ophthalmic emergency if not treated promptly and can results in permanent visual loss. Case Illustration : A 36-years-old female came to Glaucoma Unit at Cicendo National Eye Hospital with progressive blurred vision since 1 year ago, worsening in the past six months. Accompanying symptoms included pain, headache, halo, and conjunctival hyperemia. She had been diagnosed with glaucoma and received timolol maleate, acetazolamide, and glycerin. Seven days later, her visual acuity worsened to 3/60 ph 0.15 RE and 2/60 ph 0.15 LE, with high IOP in both eyes, with the higher IOP being >30 mmHg. The cup-to-disc ratio was 0.3 RE and 0,8 LE. The anterior segment showed shallow anterior chamber, mid-dilated pupil, and conjunctival injection (Figure 1.). Gonioscopy examination showed Schwalbe line of both eyes (Figure 2.). Acetazolamide was stopped, and one week later the condition resolved (Figure 3.). Discussion : Secondary angle closure glaucoma caused by acetazolamide is important to consider because most people tolerate acetazolamide well. The mechanism of closed-angle glaucoma can be pupillary block and non-pupillary block. Non-pupillary block is caused by thickening, forward movement the iris-lens diaphragm, rotation of the ciliary body, and choroidal effusion. This process is an idiosyncratic reaction to certain systemic drugs. Conclusion : Few cases were reported about secondary bilateral angle closure glaucoma due to acetazolamide. Treatment of angle closure glaucoma involves stopping acetazolamide